In Vitro Selection of Abaca for Resistance to Fusarium oxysporum f.sp. cubense - RULLY DYAH PURWATI; SAID HARRAN; SUDARSONO SUDARSONO (Bogor Agricultural University, Indonesia, 2007)
Abaca (Musa textilis Nee) is an important industrial crop. However, the cultivation of this crop in Indonesia is hampered by Fusarium wilt (Panama disease) as a result of Fusarium oxysporum f.sp. cubense (Foc) infection. The objectives of this study were to (i) evaluate inhibitory effects of culture filtrates (CF) of three Foc isolates (Banyuwangi, Malang, and Bojonegoro isolates) on shoot growth of abaca cv. Tangongon and Sangihe-1, (ii) determine sublethal concentration of Foc CF, (iii) isolate variant cells/tissues which are insensitive against Foc CF and regenerate plantlets from the variants, and (iv) evaluate responses of the plantlets against Foc infection. The results of the experiment showed that even though CF of all Foc isolates inhibited abaca’s shoot growth, CF of Foc Banyuwangi isolate showed the most inhibitory effect. Sublethal concentration of CF of Foc Banyuwangi isolate was 40%. From abaca cv. Tangongon, 326 shoots were regenerated from CF insensitive embryogenic calli while from Sangihe-1 - 176 shoots were regenerated. Following acclimatization and Foc inoculation using detached-leaf dual culture test, a total of four immune, two resistant, and two moderately resistant plantlets were identified out of 45 tested variants of Tangongon. On the other hand, only two resistant and one moderately resistant plantlets were identified out of 10 tested variants of Sangihe-1. Key words: Fusarium wilt, in vitro selection, culture filtrate, ethylmethanesulphonate (EMS), Musa textilis Nee